2005
DOI: 10.1038/modpathol.3800266
|View full text |Cite
|
Sign up to set email alerts
|

Primary breast diffuse large B-cell lymphoma shows a non-germinal center B-cell phenotype

Abstract: Primary breast diffuse large B-cell lymphoma has a poor prognosis relative to other extranodal diffuse large Bcell lymphoma. Recently, diffuse large B-cell lymphoma has been subclassified as germinal center B-cell-like and nongerminal center B-cell types using tissue microarrays. The 5-year overall survival rate of the germinal center B-cell group is better than that of the nongerminal center B-cell group. To elucidate the reason for which primary breast diffuse large B-cell lymphoma has a poor clinical outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
34
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 35 publications
10
34
2
Order By: Relevance
“…We found 71% of Bcl-2-positive tumor samples when more than 30% of the tumor cells were positive. This result was concordant with the 10/15 Bcl-2-positive PBL reported by Yoshiba et al [23] and the proportion of Bcl-2-positive DLBCLs reported in the literature [25][26][27][28][29][30][31][32][33][34][35][36]. Finally, we observed 14% of CD10 positivity suggesting a large amount of PBL of nongerminal center B-cell lymphoma (non-GCB), as shown by Yoshida et al who observed 15/ 15 non-GCB PBL [23].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found 71% of Bcl-2-positive tumor samples when more than 30% of the tumor cells were positive. This result was concordant with the 10/15 Bcl-2-positive PBL reported by Yoshiba et al [23] and the proportion of Bcl-2-positive DLBCLs reported in the literature [25][26][27][28][29][30][31][32][33][34][35][36]. Finally, we observed 14% of CD10 positivity suggesting a large amount of PBL of nongerminal center B-cell lymphoma (non-GCB), as shown by Yoshida et al who observed 15/ 15 non-GCB PBL [23].…”
Section: Discussionsupporting
confidence: 93%
“…This result was concordant with the 10/15 Bcl-2-positive PBL reported by Yoshiba et al [23] and the proportion of Bcl-2-positive DLBCLs reported in the literature [25][26][27][28][29][30][31][32][33][34][35][36]. Finally, we observed 14% of CD10 positivity suggesting a large amount of PBL of nongerminal center B-cell lymphoma (non-GCB), as shown by Yoshida et al who observed 15/ 15 non-GCB PBL [23]. Our results are therefore concordant with those that have been previously reported in PBL, as in DLBCLs [28,31,32,34,35,37] (Table III).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…MUM1 positive cases are assigned to the nongerminal center subtype and MUM1 negative tumors to the germinal center subtype. Several studies have investigated the validity of using this stratification scheme in other extranodal diffuse large B-cell lymphomas; [13][14][15][16][17][18] however, it remains unclear whether primary central nervous system diffuse large B-cell lymphomas can be subdivided into these same two prognostic groups.…”
mentioning
confidence: 99%
“…[18] Regarding laterality, although the largest study of PBL so far showed predilection of right breast involvement, as in ours, left side predilection has been reported and there was no obvious tendency of laterality reported in most other studies. [4,[20][21][22] The reason for such differences is still unknown, and the evidence of laterality predilection is limited.…”
Section: Discussionmentioning
confidence: 99%